Peningkatan Kesadaran Gotong Royong di Kalangan Masyarakat sebagai Pembangunan Desa Siunggam Tonga - Haspin Hansori; Maryam Mardia; Muhammad Yusuf; Raniati Raniati; Riski Aidah; Rohmatul Aminah Hasibuan; Samtiyathul Hasanah; Wakiah Tussukria; Tegar Wibawa Jambak (LPMP Imperium, 2024)
This educational program to develop community motivation is based on collaboration between students studying real work in Siunggam Tonga Village, Padang Bolak Tenggara District, Mandailing Natal Regency. In this program, the most hoped for goal is to provide motivation and a high level of awareness of cleanliness on the part of the community in Siunggam Tonga. KKN Stain Madina Group 29 still needs hard work and direction from village officials or government to build a spirit of mutual cooperation in the community, because the community still has low awareness of cleanliness and how to build a village that is good and independent, comfortable and peaceful. The village government and KKN STAIN Madina have tried to carry out or establish several activities such as mutual cooperation, cleaning cemeteries, cleaning prayer rooms, renovating mosques and village offices and providing a little explanation about the importance of cleanliness and togetherness between one individual and another. With the participation of the STAIN MADINA KKN in this program and actively participating in every activity that has been held during the KKN in Siunggam Tonga village, many changes have emerged, especially in the sense of kinship and togetherness that is well established.